When a house is never a home: Housing instability among youth affected by parental drug abuse. (August 2021) - Lewis, Quiana J.; Smith, Bianca D.; Offiong, Asari; Prioleau, Morgan; Powell, Terrinieka W.
Abstract: Background: The negative consequences of parental substance abuse are significant and longstanding for children. Among other risks, these youth are more likely to experience housing instability. The most common predictor of a child not living with their biological parent is parental substance use. Research shows that these youth are at higher risks of housing instability; however, little is known about their housing experiences, from their perspective. This study explored the housing experiences of youth affected by parental substance abuse. Participants and setting: Fourteen African American young adults ages 18 to 24 years old who identified having at least one biological parent with a history of substance use participated in this study. The study is based in Baltimore, MD, USA; an urban city with one of the highest rates of drug overdose and substantial disadvantage. Methods: In-depth interviews were conducted among fourteen young adults (18–24) affected by parental drug use to discuss their housing experiences throughout childhood and adolescence. Five research team members developed a codebook, double coded all transcripts and analyzed inductively using a qualitative content analytic approach. Results: Three themes emerged to characterize housing experiences: frequent housing transitions, repeated trauma exposures related to housing instability, and the lasting effects of housing instability. Conclusion: The residual impacts of parental substance use have caused youth to experience the toxic stress and trauma associated with housing instability. It is important that young people have safe, stable and reliable housing to promote child health and normative development.